Pengenalan Metode Lattice dalam Perkalian untuk Meningkatkan Motivasi Belajar Siswa SD - Deby Erdriani; Dewi Devita; Laila Marhayati (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2025)
Mastery of the concept of multiplication is a fundamental ability that needs to be mastered by primary school students as a foundation for learning further mathematical material. Unfortunately, many learners have difficulty in understanding multiplication thoroughly, both due to the abstract nature of the material and the lack of varied teaching methods. One of the main challenges is the decreased motivation to learn when facing multiplication topics that are considered complicated and boring. This programme introduces the lattice method as an alternative to learning multiplication at the primary level. This visual technique breaks down the multiplication process into structured steps that are easier to understand. The activity involved grade IV students and mathematics teachers at SDN 31 Jati Tanah Tinggi Padang as an effort to innovate numeracy learning. Implementation included socialisation, training, practice, and collaborative evaluation between teachers and students. Assessment instruments included learning interest questionnaire, comprehension test, observation sheet, and group discussion. As a result, the lattice method was proven to improve not only comprehension but also students' participation, confidence, and enthusiasm. Thus, this approach can be a solution to create more interesting and effective learning.